Elevated vitreous body glial fibrillary acidic protein in retinal diseases - Jünemann, Anselm Gerhard Maria (Graefes Arch Clin Exp Ophthalmol, 2015)
PURPOSE: Increased expression of glial fibrillary acidic protein (GFAP) is a characteristic of gliotic activation (Müller cells and astrocytes) in the retina. This study assessed vitreous body GFAP levels in various forms of retinal pathology. METHODS: This prospective study included 82 patients who underwent vitrectomy (46 retinal detachments (RDs), 13 macular hole (MHs), 15 epiretinal glioses (EGs), 8 organ donors). An established enzyme–linked immunosorbent assay (ELISA, SMI26) was used for quantification of GFAP. RESULTS: The highest concentration of vitreous body GFAP in organ donors was 20 pg/mL and it was used as the cutoff. A significant proportion of patients suffering from RD (65 %) to EG (53 %) had vitreous body GFAP levels above this cutoff when compared to organ donors (0 %, p < 0.0001, p = 0.0194, respectively, Fisher’s exact test) and MH (8 %, p < 0.0001, p = 0.0157, respectively). In RD and EG, vitreous body GFAP levels were correlated with axial length (R = 0.69, R = 0.52, p < 0.05 for both). CONCLUSIONS: The data suggest that human vitreous body GFAP is a protein biomarker for glial activation in response to retinal pathologies. Vitreous body GFAP levels may be of interest as a surrogate outcome for experimental treatment strategies in translational studies.